UNITEN Smart Programming Apps Using Combination of Robotic and Block Programming (RoBlock) - Mohd Azmi, M.S; Lim, K.C.; Mohan, P.C; Kit, T.W (2021 IEEE International Conference on Computing (ICOCO), 2021)
Block-based programming is the latest and alternative approach to attract student in learning programming subject. In many schools and universities in Malaysia, text-based programming technique is widely use to teach programming subject and most of students unable to appreciate the approach especially when the output is something intangible. Visual-based programming has been introduced to tackle student's interest in learning programming subject, however according to our finding, chances of student to lost focus is still high and it is related to the output of programming. In this study, a UNITEN Smart Programming Apps using combination robotic and block-based programming (RoBlock) is proposed. Further, the performance (student's time spent and student focus) of the text-based programming (JAVA), Scratch and RoBlock are compared. Results showed that our proposed RoBlock tools outperforms conventional way to teach programming subject and native block-based programming tools (Scratch).